Effects of Artificial Intelligence Integration on Design Mindset, Creativity, and Reflection - Khaerul Amri; Intan Novita Kowaas; Andro Ruben Runtu; Saif Mohammed; Rifky Muhajji (Academic Bright Collaboration, 2025)
Artificial intelligence (AI) is increasingly embedded in design-based learning because it can accelerate ideation, support rapid iteration, and enable human–AI collaboration; however, a persistent challenge is maintaining an appropriate balance between AI-driven automation and human agency while ensuring that students’ design mindset, creativity, and reflective thinking are genuinely strengthened. This study aimed to examine the perceived effects of AI integration on students’ design mindset, creativity, and critical reflection in higher education. A quantitative cross-sectional design was employed with purposive sampling of 96 university students (predominantly female; mean age ≈20 years) who had used AI tools in learning and design activities; data were collected via an online Likert-scale questionnaire distributed from October to November 2024 and analyzed using descriptive statistics (means and sums). The results indicate that students reported generally moderate-to-positive perceptions of AI’s contribution across all constructs, with overall mean scores suggesting beneficial support for design mindset (M≈2.59) and creativity (M≈2.59), and relatively stronger support for reflection (M≈2.68), particularly in helping students understand their learning/creative processes and learn from mistakes. These findings imply that higher education institutions such as Makassar State University should integrate AI more strategically as a co-creative learning partner, complemented by structured training for both instructors and students to maximize creative and reflective gains while safeguarding human control; overall, AI shows strong potential to enhance design-oriented learning, but deeper implementation and longitudinal evaluation are recommended.